2021
DOI: 10.1136/bmjopen-2020-043432
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive spirometry pattern and the risk of chronic kidney disease: analysis from the community-based prospective Ansan-Ansung cohort in Korea

Abstract: ObjectiveThere have been limited studies on the relationship between obstructive spirometry pattern and the development of chronic kidney disease (CKD). We investigated the association between obstructive spirometry pattern and incident CKD development in a large-scale prospective cohort study.MethodsWe reviewed the data of 7960 non-CKD adults aged 40–69 years who participated in the Ansung-Ansan cohort, a prospective community-based cohort study. Prebronchodilation results for the ratio of forced expiratory v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 11 Transgender women showed a significantly reduced FEV 1 :FVC ratio compared with cisgender women ( figure 2C ). The FEV 1 :FVC ratio has been used as a screening index for identifying obstructive lung conditions globally, 37 as a lower FEV 1 owing to obstruction of air escaping from the lungs will reduce the FEV 1 :FVC ratio. Transgender women’s results ( figure 2C ) suggest obstructed airflow in the lungs 38 when compared with cisgender women.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Transgender women showed a significantly reduced FEV 1 :FVC ratio compared with cisgender women ( figure 2C ). The FEV 1 :FVC ratio has been used as a screening index for identifying obstructive lung conditions globally, 37 as a lower FEV 1 owing to obstruction of air escaping from the lungs will reduce the FEV 1 :FVC ratio. Transgender women’s results ( figure 2C ) suggest obstructed airflow in the lungs 38 when compared with cisgender women.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of CKD was also evident among patients with obstructive airway disease irrespective of diagnosis of COPD. 14,15 In a study by Shihong et al, renal improvement was found in 30.59% of the group-D COPD but this was less than 15% in other groups. This study showed COPD patients having renal impairment had worse lung function and clinical symptoms compared with those with normal renal function.…”
Section: Resultsmentioning
confidence: 97%